2016
DOI: 10.5665/sleep.5430
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Is Significantly Inversely Associated with Disease Severity in Caucasian Adults with Obstructive Sleep Apnea Syndrome

Abstract: We observed widespread vitamin D deficiency and insufficiency in a Caucasian, OSAS population. There were significant, independent, inverse relationships between 25(OH)D and AHI as well as nocturnal HR, a known cardiovascular risk factor. Further, 25(OH)D was significantly lower in OSAS cases compared to matched, non-OSAS subjects. We provide evidence that 25(OH)D and OSAS are related, but the role, if any, of replenishment has not been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 43 publications
5
47
1
4
Order By: Relevance
“…As far as we are aware, this is the first report underlining the association between low vitamin D levels and poor SQ in renal disease. In agreement with this observation, recent data support an inverse relationship between vitamin D levels and OSA severity [21]. Furthermore, vitamin D supplementation has been linked with RLS improvement [22].…”
Section: Discussionsupporting
confidence: 76%
“…As far as we are aware, this is the first report underlining the association between low vitamin D levels and poor SQ in renal disease. In agreement with this observation, recent data support an inverse relationship between vitamin D levels and OSA severity [21]. Furthermore, vitamin D supplementation has been linked with RLS improvement [22].…”
Section: Discussionsupporting
confidence: 76%
“…[6][7][8] A recent study suggested that the association between lower 25(OH) D and OSA was largely confounded by larger BMI and neck circumference. 9 In contrast, our group 10 and others [11][12][13][14] have reported a high rate of vitamin D deficiency in OSA, where vitamin D levels (25(OH)D) are lower in severe OSA 10,11,13 and inversely correlate with some of its associated metabolic alterations, including abnormal glucose metabolism 11,12 as well as nocturnal heart rate. 10 Vitamin D receptors are located systemically and recent advances have demonstrated the potential of vitamin D to influence a wide variety of organs.…”
mentioning
confidence: 50%
“…9 In contrast, our group 10 and others [11][12][13][14] have reported a high rate of vitamin D deficiency in OSA, where vitamin D levels (25(OH)D) are lower in severe OSA 10,11,13 and inversely correlate with some of its associated metabolic alterations, including abnormal glucose metabolism 11,12 as well as nocturnal heart rate. 10 Vitamin D receptors are located systemically and recent advances have demonstrated the potential of vitamin D to influence a wide variety of organs. There is preliminary evidence that vitamin D supplementation may attenuate some metabolic disturbances through antiinflammatory, antihyperglycemic, and antihyperlipidemic roles, although these potential effects are inconsistent and controversial.…”
mentioning
confidence: 50%
See 2 more Smart Citations